Consensus reaching process under interval-valued hesitant fuzzy environment. (February 2023) - Liang, Wei; Labella, Álvaro; Wang, Ying-Ming; Rodríguez, Rosa M.
Abstract: This paper introduces a consensus reaching process (CRP) able to smooth disagreements between the experts who participate in a multi-criteria group decision-making problem in order to obtain a solution in which experts agree. To deal with the lack of information and uncertainty inherent in this type of problems, the experts' preferences are modeled by means of interval-valued hesitant fuzzy sets (IVHFS), which allow both representing uncertainty and any doubts experts may have when giving their assessments over the alternatives. The proposal makes use of an extension of the ordered weight averaging operator under an IVHFS which performs aggregations reasonably. In addition, the CRP incorporates a feedback mechanism that provides precise and individual suggestions to the experts for increasing the level of agreement within the group. Finally, the proposal is validated by solving a practical study related to the selection of renewable energies in China under several scenarios. Highlights: An EVR-IVHFOWA operator is defined. A consensus reaching process for IVHFS is firstly proposed. A feedback mechanism that guides the consensus process is introduced. A simulation of three scenarios to verify the feasibility of the proposed model is shown.